2018
DOI: 10.1002/hbm.24242
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state pulvinar‐posterior parietal decoupling in PTSD and its dissociative subtype

Abstract: Key evidence points toward alterations in the neurocircuitry of large-scale networks among patients with posttraumatic stress disorder (PTSD). The pulvinar is a thalamic region displaying reciprocal connectivity with the cortex and has been shown to modulate alpha synchrony to facilitate network communication. During rest, the pulvinar displays functional connectivity with the posterior parietal cortex (PPC), a heteromodal network of brain areas underlying multisensory integration and socioaffective functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 102 publications
(197 reference statements)
3
28
0
Order By: Relevance
“…Although the Brainnetome atlas was used to parcellate the insula into its subregions (not captured in the Automated Anatomical Labeling [AAL] atlas and MNI2 Talairich [MNI2Tal] atlas), brain regions from the results of the seed‐based analysis were identified using the AAL atlas (Tzourio‐Mazoyer et al, ) via xjview software (https://www.nitrc.org/projects/xjview), the MNI2Tal atlas (https://bioimagesuite.yale.edu/mni2tal; Lacadie, Fulbright, Constable, & Papademetris, ), and visual inspection using an additional anatomical atlas (Montemurro & Bruni, ). This approach is consistent with our previous studies (Harricharan et al, ; Rabellino et al ; Terpou et al, ).…”
Section: Methodssupporting
confidence: 94%
See 2 more Smart Citations
“…Although the Brainnetome atlas was used to parcellate the insula into its subregions (not captured in the Automated Anatomical Labeling [AAL] atlas and MNI2 Talairich [MNI2Tal] atlas), brain regions from the results of the seed‐based analysis were identified using the AAL atlas (Tzourio‐Mazoyer et al, ) via xjview software (https://www.nitrc.org/projects/xjview), the MNI2Tal atlas (https://bioimagesuite.yale.edu/mni2tal; Lacadie, Fulbright, Constable, & Papademetris, ), and visual inspection using an additional anatomical atlas (Montemurro & Bruni, ). This approach is consistent with our previous studies (Harricharan et al, ; Rabellino et al ; Terpou et al, ).…”
Section: Methodssupporting
confidence: 94%
“…Seedbased analysis correlations with self-reported psychological measures used to assess state symptoms at the time of scanning (RSDI, STAI, CADSS) and trait symptoms prior to scanning (CAPS, CTQ, MDI, BDI) were performed in both the PTSD and PTSD+DS groups (significant peak coordinates were evaluated at the same voxel-wise pFWE < .05, k = 10 threshold and visual inspection using an additional anatomical atlas (Montemurro & Bruni, 1988). This approach is consistent with our previous studies (Harricharan et al, 2016;Rabellino et al 2018;Terpou et al, 2018).…”
Section: Full Factorial Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…In effect, subcortical systems functioning with reduced cortical input may form defensive responses stored in subcortical “loops” within the midbrain (Lanius, Paulson, et al, ). Here, the thalamus serves as a mediator between the cortex and the lower‐level systems and the thalamus has further been demonstrated to display altered functionality in PTSD and its dissociative subtype (Lanius et al, ; Terpou et al, ). Specifically, the thalamus shows less activation in PTSD as compared to controls (Lanius et al, ), a finding supported by a previous meta‐analysis pointing toward thalamic hypoactivation in general in PTSD (Etkin & Wagner, ).…”
Section: Tonic Immobilitymentioning
confidence: 99%
“…These studies explored the role of pulvinar under specific task conditions, leaving open the question as to whether the pulvinar influence on cortico-cortical functional connectivity is related to engagement in specific tasks, or rather a more basic property of large-scale network connectivity. Studies in humans have suggested functional connectivity between pulvinar and cortical areas even in the absence of any active task structure, based on BOLD responses (Stein, 2000;Barron, 2015;Terpou, 2018). Watching short movie clips during the data collection keeps subjects more engaged and has been shown to be a reliable method for obtaining functional connectivity data both in monkeys (Mantini, 2013) and in humans (Vanderwal, 2015;Vanderwal, 2019).…”
Section: Discussionmentioning
confidence: 99%